Nutrient intakes of pregnant and lactating women in Indonesia and Malaysia: Systematic review and meta-analysis - Agustina, Rina; Rianda, Davrina; Lasepa, Wanda; Birahmatika, Fitya S.; Stajic, Vladimir; Mufida, Rachmi (Frontiers in Nutrition, 2023)
Introduction: Optimizing intake during pregnancy and lactation is crucial to the growth and development of children and their lifelong health. We performed a systematic review and meta-analysis to describe the nutrient intake among pregnant and lactating women in Indonesia and Malaysia, the countries experiencing rapid nutrition transition in Southeast Asia. Methods: We screened 2258 studies published between January 1980 and March 2021. The nutrient intakes of pregnant and lactating women were analyzed descriptively and calculated the percentage of adequacy using the national recommended daily allowance/nutrient intake and estimated average requirements (EAR). Standardized mean differences (SMD) of the meta-analysis were reported for selected nutrients. Results: Fifty-three studies exhibited that energy and macronutrient intake among pregnant and lactating women in both countries were below the recommendations, including protein (SMD -2.26; 95%CI; -2.98, -1.54 for pregnant and -0.67; 95%CI -15.7, -11.5 for lactating women) except for Malaysian women in limited studies. Most studies reported pregnant and lactating women failed to meet the EAR for vitamin D (≤70% EAR), E (≤50% EAR), and all water-soluble vitamins (<60% EAR, except for vitamin C among Malaysian). Moreover, calcium, iron, and potassium intake among pregnant women were notably low. Phosphorus intake in both countries and sodium intake among Malaysian pregnant women exceeded the EAR. A similar trend was observed in the meta-analysis on low intake of vitamin D, C, calcium, and iron, but sufficient in vitamin A, zinc, and phosphorus. Conclusion: Indonesian and Malaysian pregnant and lactating women had insufficient intake of essential nutrients. Innovative research and programs should be developed to improve maternal nutrition.